The Influence Of Organo-Mineral Composts On The Dynamics Of The Opening Of Cotton Bolls In Saline Soil Conditions - Zinatdinov Kamalatdiyin Mnajatdin uli (Zien Journals, 2023)
In the article, the effect of organo-mineral compost, manure and mineral fertilizers on the opening dynamics of cotton bolls was determined. In this, the positive effect of organic fertilizers and organo-mineral composts on the water-physical and agrochemical characteristics of the soil and the dynamics of the opening of cotton bolls by increasing its productivity were explained.
Keywords: Soil; organo-mineral compost; manure; fertility